The prevalence of malaria in people living with HIV in Yaounde, Cameroon - Anna Longdoh Njunda; Charles Njumkeng; Shey Dickson Nsagha; Jules Clement Nguedia Assob; Tebit Emmanuel Kwenti (BMC, 2016)
Abstract Background Coinfection with malaria and HIV is common in Sub-Saharan Africa. In the advent of a decline in the global incidence of malaria, it is important to generate updated data on the burden of malaria in people living with HIV (PLWHIV). This study was designed to determine the prevalence of malaria in PLWHIV in Yaounde, Cameroon, as well determine the association between CD4 + T cell count and malaria in the study population. Methods In a cross sectional study performed between April 2015 and June 2016, 355 PLWHIV were enrolled and blood samples were collected for analysis. Complete blood count was performed using an automated haematology analyser (Mindray®, BC-2800) and CD4 + T cell count was performed using a flow cytometer (BD FASCount™). Giemsa-stained blood films were examined to detect malaria parasite. The Pearson's chi-square, student's T-test, ANOVA, and correlation analysis were all performed as part of the statistical analyses. Results The prevalence of malaria observed in the study was 7.3 % (95 % CI: 4.8-10.6). No significant association was observed between the prevalence of malaria and age or gender. The prevalence of malaria was higher in participants who were not sleeping in insecticide treated bed nets, ITNs (p < 0.001); and in participants who were not on cotrimoxazole prophylaxis (p = 0.002). The prevalence of malaria (p < 0.001) and malaria parasite density (p = 0.005) were observed to be progressively higher in participants with CD4 + T cell count below 200cells/μl. Furthermore, the mean CD4 + T cell count was observed to be lower in participants coinfected with malaria compared to non-coinfected participants (323.5 vs 517.7) (p < 0.001). In this study, a negative correlation was observed between malaria parasite density and CD4 + T cell count (p = 0.019). Conclusions A low prevalence of malaria was observed in the study population. Some of the factors accounting for the low prevalence of malaria in this study population may include the health seeking habit of PLWHIV, the use of cotrimoxazole based chemoprophylaxis, and their cautious use of ITNs.